Exogenous Crosslinking Restores Intradiscal Pressure of Injured Porcine Intervertebral Discs: An In Vivo Examination Using Quantitative Discomanometry. Issue 20 (15th October 2015) - Lin, Hsiu-Jen; Lin, Leou-Chyr; Hedman, Thomas P.; Chen, Weng-Pin; Chuang, Shih-Youeng
Abstract : Study Design: In vivo examination of intradiscal pressure by quantitative discomanometry (QD). Objective: To determine whether an injectable, exogenous crosslinking could acutely restore intradiscal pressure of stab-injured discs in vivo by short-term treatment. Summary of Background Data: Disc biomechanical performance depends on its integrity associated with the intradiscal pressure and mechanical properties. Genipin crosslink augmentation has demonstrated the in vitro biomechanical capability to improve intervertebral joint stability and increase mechanical properties of the annulus fibrosus. Methods: 4 lumbar discs on each of 8 swine were randomly assigned to 4 groups: intact, injured, untreated, and crosslinked. A 16G needle was stabbed into the annulus fibrosus to create the disc injury model. An injection of 0.33% genipin solution was delivered into the annulus to treat the injury. QD technique was performed to examine the intradiscal pressure for the intact and injured discs at the time of surgery, while untreated and crosslinked discs were measured 1-week postsurgery. 4 QD parameters were analyzed and compared across the 4 groups: leakage pressure and volume, and saturation pressure and volume. Results: The leakage and saturation pressures of the injured group were significantly lower than those of the intact group ( P = 0.004 and P = 0.01, respectively). The leakage and saturation pressures of untreated discs were statistically equivalent to the injured levels, but with a 2-times higher saturation volume. Relative to the untreated group, the leakage pressure and saturation pressure of genipin-crosslinked discs had a 617% ( P = 0.008) and a 473% increase ( P = 0.007), respectively. Conclusion: A large disc injury produced by annular puncture immediately lowered intradiscal pressure when left untreated. Genipin crosslinking can restore intradiscal pressure acutely in vivo without any obvious morbidity associated with the injection. Level of Evidence: N/A Abstract : Genipin is Generally Recognized As Safe (GRAS) by the Food and Drug Administration and showed beneficial outcomes during in vitro biomechanical testing. This in vivo study demonstrated with quantitative discomanometry that genipin crosslinking could restore intradiscal pressure of stab-injured discs. The data support genipin's potential for early treatment of injured discs.